2019
DOI: 10.3390/genes10100753
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alternatively-Activated Pathways between Primary Breast Cancer and Liver Metastatic Cancer Using Microarray Data

Abstract: Alternatively-activated pathways have been observed in biological experiments in cancer studies, but the concept had not been fully explored in computational cancer system biology. Therefore, an alternatively-activated pathway identification method was proposed and applied to primary breast cancer and breast cancer liver metastasis research using microarray data. Interestingly, the results show that cytokine-cytokine receptor interaction and calcium signaling were significantly enriched under both conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 81 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…S5d). Among the top 8 KEGG pathways, cytokine-cytokine receptor interaction, the TNF signaling pathway and the NOD-like receptor signaling pathway are known to play roles in breast cancer [36][37][38] . In addition, to obtain insight into the relationship between up-regulated Rad21 and breast cancer, we subjected breast cancer cell lines to gene set enrichment analysis (GSEA).…”
Section: Rad21 Up-regulation Is Involved In Breast Cancer By Affecting Chromatin Architecturementioning
confidence: 99%
“…S5d). Among the top 8 KEGG pathways, cytokine-cytokine receptor interaction, the TNF signaling pathway and the NOD-like receptor signaling pathway are known to play roles in breast cancer [36][37][38] . In addition, to obtain insight into the relationship between up-regulated Rad21 and breast cancer, we subjected breast cancer cell lines to gene set enrichment analysis (GSEA).…”
Section: Rad21 Up-regulation Is Involved In Breast Cancer By Affecting Chromatin Architecturementioning
confidence: 99%
“…In support of our results, studies have demonstrated that E2F4 function as crucial regulator in liver cancer 38 . The increased E2F4 in breast cancer is also associated with breast cancer liver metastasis 39 . it is also estimated that E2F4 acts as bridging genes in the process of colorectal cancer liver metastasis 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the cytokine-cytokine receptor pathway, as the top-ranked pathway, stimulated our interest. Previous researches have shown that cytokine-cytokine receptor interaction is significantly associated with many biological processes of BC, such as chemoresistance and metastasis of BC (26,27), which often leads to poor prognosis of patients with BC. In addition, MAPK signaling pathway (27), B cell receptor signaling pathway (28), and chemokine signaling pathway (29) are also important roles that affect the OS of patients with BC.…”
Section: Discussionmentioning
confidence: 99%